Smartphone Use, Technology Affordance for Healthcare and Elders' Life Satisfaction - Li, Geling; Jin, Chenfei; Zhao, Bin; Wu, Bao (Frontiers in Public Health, 2022)
Previous studies have examined how smartphones influence the life satisfaction of the elderly, but the existence of conflicting conclusions suggests the existence of a “black box”. In this study, sample of 941 seniors, we examine whether smartphone use can improve life satisfaction by improving emotional affordance and functional affordance. We found that living with adult children influenced the positive impact of smartphone use on functional affordance, but there was no significant effect on emotional affordance. This study contributes to our understanding by identifying a mechanism that is based on the selective optimization with compensation (SOC) framework to explain how cross-technology usage facilitates aging well.